2000
DOI: 10.1111/j.1755-618x.2000.tb00587.x
|View full text |Cite
|
Sign up to set email alerts
|

First Person Accounts and Sociological Explanations of Delinquency*

Abstract: Cinquante‐six garçons du secondaire ont expliqué pourquoi ils avaient perpétré ou non certains actes de délinquance (combat, vandalisme, vol à l'étalage, usage de drogues). Ils ont aussi ciblé des théories sociologiques de la délinquance qui s'appliquent à leur comportement. Leurs réponses montrent que les deux types de données se recoupent beaucoup. L'effort, la théorie gánérate, les pairs, le contrôle social, les techniques de neutralisation et la prévention sont importants, mais non l'étiquetage ni l'imitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…Babin and Babin (1996) suggested a need to encourage moral development in young children. Teevan and Dryburgh (2000) proposed use of first person accounts by male high school students to determine strain and control theory which are parts of delinquency paradigms. Forney and Crutsinger (2001) suggested that socialisation, age, and gender influence decision of a perpetrator to shoplift.…”
Section: Literature From Sociologymentioning
confidence: 99%
“…Babin and Babin (1996) suggested a need to encourage moral development in young children. Teevan and Dryburgh (2000) proposed use of first person accounts by male high school students to determine strain and control theory which are parts of delinquency paradigms. Forney and Crutsinger (2001) suggested that socialisation, age, and gender influence decision of a perpetrator to shoplift.…”
Section: Literature From Sociologymentioning
confidence: 99%
“…Examples of its application include delinquency and crime (e.g. Teevan and Dryburgh, 2000), violence and aggression (e.g. Cavanagh et al, 2001), workplace deviance (e.g.…”
Section: Neutralization Theorymentioning
confidence: 99%
“…Issues with design have also been identified (Gibbs, Giever, & Martin, 1998), as a number of studies indicating support are based on problematic samples (Teevan & Dryburgh, 2000). The issue here is that results are obtained from samples drawn from college classes (Gibbs et al, 1998;Simpson & Leeper-Piquero, 2002), selective samples of "street youths" (Baron, 2003), adults approached in their homes or malls (Tittle & Botchkovar, 2005a), or small inmate populations (De-Li, 2005).…”
mentioning
confidence: 99%